The 852/3 CE Mount Churchill eruption: examining the potential climatic and societal impacts and the timing of the Medieval Climate Anomaly in the North Atlantic region - Mackay, Helen; Plunkett, Gill; Jensen, Britta J. L.; Aubry, Thomas J.; Corona, Christophe; Kim, Woon Mi; Toohey, Matthew; Sigl, Michael; Stoffel, Markus; Anchukaitis, Kevin J.; Raible, Christoph; Bolton, Matthew S. M.; et al. (Climate of the Past, 2022)
The 852/3 CE eruption of Mount Churchill, Alaska, was one of the largest first-millennium volcanic events, with a magnitude of 6.7 (VEI 6) and a tephra volume of 39.4–61.9 km3 (95 % confidence). The spatial extent of the ash fallout from this event is considerable and the cryptotephra (White River Ash east; WRAe) extends as far as Finland and Poland. Proximal ecosystem and societal disturbances have been linked with this eruption; however, wider eruption impacts on climate and society are unknown. Greenland ice core records show that the eruption occurred in winter 852/3 ± 1 CE and that the eruption is associated with a relatively moderate sulfate aerosol loading but large abundances of volcanic ash and chlorine. Here we assess the potential broader impact of this eruption using palaeoenvironmental reconstructions, historical records and climate model simulations. We also use the fortuitous timing of the 852/3 CE Churchill eruption and its extensively widespread tephra deposition of the White River Ash (east) (WRAe) to examine the climatic expression of the warm Medieval Climate Anomaly period (MCA; ca. 950–1250 CE) from precisely linked peatlands in the North Atlantic region. The reconstructed climate forcing potential of the 852/3 CE Churchill eruption is moderate compared with the eruption magnitude, but tree-ring-inferred temperatures report a significant atmospheric cooling of 0.8 ∘C in summer 853 CE. Modelled climate scenarios also show a cooling in 853 CE, although the average magnitude of cooling is smaller (0.3 ∘C). The simulated spatial patterns of cooling are generally similar to those generated using the tree-ring-inferred temperature reconstructions. Tree-ring-inferred cooling begins prior to the date of the eruption suggesting that natural internal climate variability may have increased the climate system's susceptibility to further cooling. The magnitude of the reconstructed cooling could also suggest that the climate forcing potential of this eruption may be underestimated, thereby highlighting ...